Diagnostic Accuracy of Magnetic Resonance Imaging in Detecting Placenta Accrete Keeping Post-Operative Histopathology Findings as a Gold Standard - Balooch, Salahuddin; Javed, Sana; Niazi, Najam us Saqib; Zafar, Kiran; Haider, Amir Hayat; Amir, Muhammad Omar (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine the diagnostic accuracy of MRI in diagnosing placenta accrete with post-operative histopathological findings considered a gold standard.Study Design: Cross-sectional study.Place and Duration of study: Combined Military Hospital, Kharian Pakistan, from Jan to Dec 2020.Methodology: In total, 119 individuals suspected of placenta accreta were evaluated with the help of magnetic resonance imaging (MRI). However, confirmation for 71 patients was obtained based on clinical criteria at the time of delivery.Results: The mean age of women was 28.67±5.64 years, and the mean gestational age for the foetus was 33.14±1.74 weeks. The present study showed that MRI has 90(141%) sensitivity, 91(66%) specificity, 94(11%) positive predictive value (PPV), and 86(27%) negative predictive value (NPV) and diagnostic accuracy of 90(75%) for diagnosing placental accreta.Conclusion: It is concluded that the use of MRI should be encouraged as an efficient and primary diagnostic tool for placenta accreta.